Pengaruh Media Sosial Influencer Terhadap Minat Beli Konsumen Melalui Promosi Produk Kosmetik di Jakarta - Dwi Puji Astuti; Donant Alananto Iskandar (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine how much influence of influencer social media on consumer buying interest through the promotion of Emina cosmetic. This research is a quantitative program with a sample of 150 respondent, who live in Jakarta and Bekasi, who have used Emina cosmetic product using nonprobability sampling and purposive sampling techniques. The results of this study indicate that the direct effect is greater than the indirect effect, because the influence of influencer social media is greater than promotion. The benefit of this research for Emina cosmetic is to increase consumer buying interest through promotion by influencer social media.